Oscillation stability enhancement using multi-objective swarm based technique for smib system - N. A. M. Kamari; I. Musirin; M. K. M. Zamani; S. A. Halim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper discussed the impact of multi-objective function in a swarm-based optimization approach for modulate proportional-integral-derivative (PID) controller parameters of a static var compensator (SVC) in a single machine infinite bus (SMIB) system. SVC is a Flexible Alternating Current Transmission Systems (FACTS) devices which often used to increase the damping of the synchronous generator. In this paper, three parameters of PID controller: proportional gain, KP, interval gain, KI and derivative gain, KD are tuned with particle swarm optimization (PSO) approach. One multi-objective function (MO) that derived from the consolidation of maximum damping factor, σmax and minimum damping ratio, ξmin is proposed to elevate the damping capability of the systems. Validation with respect to speed response and eigenvalues verification proved that the proposed MO is more competent than single objective function.